ASSESSING THE IMPACT OF SERVICE BENEFITS AND EDUCATIONAL TRANSFORMATION ON CONSUMER-BASED BRAND EQUITY (CBBE) IN HIGHER EDUCATION INSTITUTES: A MULTI-DIMENSIONAL ANALYSIS ACROSS AGE GROUPS - Devle, Amey; Chauhan, Vilas (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India’s higher education system, one of the largest worldwide, has grown significantly, now comprising over 1,000 universities and 42,000 colleges. This study explores how service benefit dimensions—employability, personal development, passion pursuit, and sociability/networking—shape Consumer-Based Brand Equity (CBBE) in Indian Higher Education Institutes (HEIs). Data collected from 190 students at two universities in Gujarat reveals that employability has the strongest influence on CBBE, highlighting the importance of career-focused services. Opportunities for passion exploration, social connections, and personal growth further enhance institutional branding, positioning HEIs competitively in a crowded education landscape.